Developing Online Learning Media Using Task Based Language Teaching and Android Video on Writing Action Research Proposal - Lestariningsih, Enny Dwi; Wijayatiningsih, Testiana Deni; Uswatun Khasanah, Dian Ratu Ayu; Setiawan, Anjar (Universitas Negeri Semarang, 2022)
Due to the pandemic situation, there is a shift in the scientific writing learning process. The process changes from offline to online, where lecturers and students must be more active and involved in the learning process through website tutorials with Microsoft Teams application synchronously and asynchronously through LMS UT. However, such a learning process also experiences problems both with wifi or the internet and the involvement and motivation of students in following it. To complete asynchronously using LMS UT, the research team focused on developing online learning media based on Task-based Language Teaching and android video. This study aims to create online learning media based on Task-Based Language Teaching and android video on writing material for Classroom Action Research to improve understanding and writing Classroom Action Research. The subjects of this research are 3rd-semester students at the Open University. The research method is the development method using a modified 4-D model of instructional development of Thiagarajan, Semmel, and Semmel (4-D model). The process of data collection is done by interview, observation, and filling out a questionnaire. The results of developing online learning media based on Task-Based Language Teaching and android video are suitable for the hybrid writing learning process. Students can be communicative in the web tutorial process. Student learning outcomes are already above the average indicator of 75% through the developed learning media. In addition, students responded positively in their involvement in the learning process using Task-Based Language Teaching-based media and android video.